Asuhan Keperawatan Gerontik Pada Pasien Demensia Dengan Pemberian Intervensi Terapi Senam Otak Untuk Meningkatkan Fungsi Kognitif Di Panti Werdha Kasih Ayah Bunda Tangerang 2023 - Devi Sri Rahayu; Siti Robeatul Adawiyah; Rina Puspita Sari; Siti Rahayu (STIKes Ibnu Sina Ajibarang, 2023)
Beckground: Increasing age in the elderly, the elderly will also experience health problems, one of the problems that often arise in the elderly is a decrease i cognitive function can affect a persons level of idependence, impaired cognitivefunction can affecta persons level of independence. Impaired cognitive fuction often has an impect on the social, psychological and physical activities of theelderly. Psychologically, this cognitive disorder can make the elderly experince frustation and depresssion. Purpose: the aim of this author is to provide an overview of the results of nursing care for dementia patients in improving cognitive function with brain exercise therapy. Methodology: casestudy design using nursing care. This case study sample used 1 patient. Planning: researchers are using brain gymnastics to improve cognitive fuction in people with dementia. Results: besed on the implementation results on Mr. I with the application of brain exercis therapy for 5 days obtalned data for measuring the use ofthe MMSE study, namely before brain exercise was performed a score of 16 (severe cognitive impairment), whereas after brain exercise was performed a value of 26 (on cognitive impairment), and it can be concluded that there is an increase cognitive fuction, this shows the influence of brain exercise in improving cognitive function in the elderly.